NUMERICAL SOLUTION FOR HYDROMAGNATIC FLUID FLOW BETWEEN TWO HORIZONTAL PLATES, BOTH THE PLATES BEING STRETCHING SHEETS - Hussain, S.; Kamal, M. A. (The Nucleus, 2014)
Numerical solution for the flow of an incompressible, steady and viscous electrically conducting fluid between two horizontal parallel non-conducting plates, the lower one is a stretching sheet and the upper one is a porous stretching sheet is found. The effects of flow parameters namely M the magnetic parameter, ï¬ the suction parameter and R the Reynolds number have been observed on velocity profiles. Similarity transformations have been used. The resulting ordinary differential equations are solved by using SOR method and Simpsonâ€™s (1/3) rule. The results have been improved by Richardson extrapolation. The numerical scheme is straightforward, easy to program and very efficient.